Effect of Early Period of Postoperative Rehabilitation in Individuals with Transverse Patellar Fractures Treated by Tension Band with Kirschner - Zhongyi FANG; Shuai FAN; Xin JIANG; Lili XU; Likun LIU (康复学报)
Objective:To evaluate the effect of one-to-one exercise therapy for transverse patellar fractures in early preriod of postoperation of tension band with kirschner wire fixation.Methods:Thirty-five consecutive patients with transverse patella fractures treated by tension band and kirschner wires were randomly assigned to rehabilitation group (n=18) or control group (n=17). Rehabilitation group received 2-week early postoperative exercise therapy, while the control group received postoperative education. All subjects were evaluated after 2-week treatment. Evaluation of knee function included range of motion (ROM) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC).Results:Compared with control group, subjects with 2-week rehabilitation showed better knee flexion ROM and lower WOMAC pain and function scores (P<0.05).Conclusion:Positive exercise therapy in early postoperative period has good effect on knee joint function recovery and quality of life improvement for patients with transverse patella fractures.